Poling Field Induced Phase Transitions in [111]-oriented (1-x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 - Shabbir, G. (The Nucleus, 2017)
The effect of poling field on phase transitions of (1-x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 (PMN-xPT) [111]-oriented single crystal was examined through temperature dependent complex capacitance study. Two first order phase transitions from paraelectric cubic to ferroelectric tetragonal and then to ferroelectric rhombohedral phases were observed in the unpoled crystal. An additional low temperature anomaly was also observed at a temperature of 40 oC in the field poled crystal. The new anomaly was associated to the field assisted monoclinic phase due to rotation of polarization vector.